Pengaruh Pemakaian CDI Type DC Terhadap Performa Mesin Kendaraan Honda Supra 100cc - Kurniawan Rahmanto (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
An internal combustion engine is a device that functions to convert thermal energy from burning fuel into mechanical energy. The Cdi ignition system is an electronic ignition system that works by utilizing a capacitor charge and discharge. CDI variations have an influence on engine torque on motorcycle engines. At 5700 rpm the motor uses a standard CDI the resulting torque is 7.11 Nm, and on a racing CDI the torque generated is 7.45 Nm at 5900 rpm. The standard CDI generated power is 6.64 hp at 7500 RPM, pan at the resulting CDI racing power is 6.79 at 7300 RPM. From the results above the standard and racing power has a difference of (2.25%) and the standard and racing torque has a difference of (4.78%). Overall using this CDI is designed to be more aggressive than standard CDI. of the two CDIs that have been tested, the racing cdi has a performance value on a 100cc Honda Supra motorcycle engine.